2019
DOI: 10.1177/1060028019830788
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of the Integrase Inhibitors Elvitegravir and Dolutegravir in Pregnant Women With HIV

Abstract: Objective: To synthesize data on the pharmacokinetics and safety of dolutegravir and elvitegravir in pregnant women living with HIV. Data Sources: A PubMed, EMBASE, Web of Science, and Google Scholar literature search (January 2010 to December 2018) was performed using the search terms dolutegravir, elvitegravir, women, pregnant*, and HIV. Additional reports were identified from conference abstracts and review of reference lists. Study Selection and Data Extraction: English-language studies reporting pharmacok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Peri-conception exposure to RAL is not associated with NTD and therefore remains the only INSTI recommended in high-income countries for women during the peri-conceptional period or during pregnancy (DHHS (USA), the European AIDS Clinical Society [] and Canadian guidelines [74]). Further trials on efficacy and tolerability are needed on the use of RAL QD 1200 mg in this population [69].…”
Section: Instis and Pregnancymentioning
confidence: 99%
“…Peri-conception exposure to RAL is not associated with NTD and therefore remains the only INSTI recommended in high-income countries for women during the peri-conceptional period or during pregnancy (DHHS (USA), the European AIDS Clinical Society [] and Canadian guidelines [74]). Further trials on efficacy and tolerability are needed on the use of RAL QD 1200 mg in this population [69].…”
Section: Instis and Pregnancymentioning
confidence: 99%
“…This study demonstrates that standard elvitegravir and cobicistat dosing during pregnancy results in significantly lower exposure, which may increase the risk of virologic failure and mother‐to‐child transmission. (Table 3) Several case studies have also shown significantly decreased elvitegravir exposure in pregnant women 62,63 . Importantly, elvitegravir C min values observed during pregnancy (16.8 and 18.3 ng/mL) are well below the concentration that inhibits 95% of viral replication of 45 ng/mL.…”
Section: Pharmacokinetics Of Cobicistat‐boosted Regimens In Pregnancymentioning
confidence: 98%
“…(Table 3) Several case studies have also shown significantly decreased elvitegravir exposure in pregnant women. 62,63 Importantly, elvitegravir C min values observed during pregnancy (16.8 and 18.3 ng/mL) are well below the concentration that inhibits 95% of viral replication of 45 ng/mL. Due to the current evidence demonstrating significantly reduced and likely subtherapeutic plasma concentrations of elvitegravir/cobicistat, the FDA currently discourages the use of elvitegravir/cobicistat during pregnancy.…”
Section: Pharmacokinetics Of Cobicistat-boosted Regimens In Pregnancymentioning
confidence: 99%
“…reduced exposure to antiretroviral agents of pregnant women living with HIV has been recently reported for darunavir, rilpivirine, cobicistat, elvitegravir, and dolutegravir. [85][86][87] Additionally, the understanding of antiretroviral placental and breastmilk transfer may offer additional insight into the potential role in preventing HIV transmission in utero and ensuring safety of in utero and breastmilk antiretroviral exposures in infants; furthermore, it may also have implications regarding viral resistance in cases where transmission does occur (reviewed in 88 ).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…In our case, the newborn-to-mother ratio for dolutegravir was 4-fold higher than the data reported in literature. 86,87 Similarly, great inter-individual variations in the newborn/mother drug ratio have…”
Section: A C C E P T E Dmentioning
confidence: 99%